ABUNDANCE AND POPULATION DYNAMICS OF THE MAJOR INSECT PESTS OF DATE PALM UNDER THE DATE PALM- FORAGE INTERCROPPING SYSTEM - K. A. Asiry; N. A. H. Alkenani; H.A. Alshehri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The objective of this study was to investigate the influence of blue panic (Panicum antidotale Retz.) and alfalfa (Medicago sativa L.) growth around palm trees on insect pests. Four experimental treatments were employed to develop fodder around date palms in the field: alfalfa, blue panic, combination of alfalfa and blue panic, and a palm monoculture without any fodder. Each treatment consisted of six replications, resulting in a total of 24 date palms examined. Insect pests were collected biweekly utilizing light and pitfall traps from January to December 2020. A one-way ANOVA was used to evaluate the effect of fodder treatments on the number of pests collected. Additionally, an ANOVA with repeated measures was used to analyze the impact of time on the quantity of insects collected across various fodder treatments. Each of these analyses was performed through SAS version 9.2. The study’s findings demonstrated that most palm pests, such as Oryctes elegans, Phonapate frontalis, Sphenophorus parumpunctatus, Xyleborus perforans, and Tenebroides mauritanicus, significantly decreased with the introduction of fodder cultivations around the examined date palms. Additionally, the data demonstrated a highly significant difference over time and the fodder treatments on several insect pests, including P. frontalis, X. perforans, and O. elegans.